The Possibility of Using Waste from Dye Sorption for Methane Production - Anna Nowicka; Tomasz Jóźwiak; Marcin Zieliński (Energies)
The aim of this study was to determine the effect of sorption of Basic Red 46 (BR46) dye by lignocellulosic biomass on the susceptibility of the sorbed waste to anaerobic decomposition by anaerobic digestion. The research material used in the experiment consisted of two types of biomass: stalks with leaves and inflorescences after mowing Canadian goldenrod (Solidago canadensis L.) (GB), and rapeseed hulls (RHs) after oil pressing. During the anaerobic decomposition of RHs, 732.30 NmL/gVS and 646.63 NmL/gVS of methane were obtained from the non-sorbed substrate and the plant material after dye sorption, respectively. Similarly, in the variants using Canadian goldenrod, the production was 220.70 NmL/gVS and 183.20 NmL/gVS. The GB sorbent sorbed 34% more BR46 dye than the RH sorbent, which is likely to have resulted in the accumulation of VFA and contributed to the partial inhibition of methane production. In light of the obtained results and the literature data, it is concluded that there is a possibility of effective use of dye sorption waste for methane production.